Healthy Roots of Community: Social Empowerment in Inclusive Health Service Practices - Kimberley Maharani Maulibulung Hutapea; Dwight Mahaputera Marulitua Hutapea (PT. Anagata Sembagi Education, 2025)
This study examines the dynamics of social empowerment in inclusive health service practices in Medan City using a descriptive qualitative approach. The background of this study stems from structural inequalities in access to and quality of health services, which place marginalized communities as passive recipients of health programs. Although the rhetoric of participation and inclusivity is often emphasized in policy documents, field practice demonstrates the dominance of a top-down approach that fails to adequately consider local values, power relations, and the socio-cultural context of the community. Through in-depth observations and interviews in several sub-districts such as Medan Marelan, Belawan, and Tembung, this study uncovers the importance of transforming the role of cadres and communities as active subjects who independently manage the health agenda. Thematic analysis results indicate that the success of equitable and inclusive service delivery depends heavily on genuine community involvement throughout the program cycle and the recognition of local knowledge as social capital. Approaches such as Community-Based Participatory Research (CBPR) and Asset-Based Community Development (ABCD) have proven relevant in building democratic and equitable health practices. This research emphasizes that health service must be a dialectical space that encourages social transformation, not simply an administrative instrument that reproduces inequality.